PENGARUH RADIASI CAHAYA TERHADAP PANEL SURYA DAN BATERAI LITHIUM-ION PADA ROBOT PENGANTAR MAKANAN (STUDI EKSPERIMEN INDOOR DAN OUTDOOR) - Halim Vizar, Mhd. Raqhil; Arif Adlie, Taufan; Amin, Muhammad (Fakultas Teknik Universitas Samudra, 2025)
This research utilizes solar energy to generate electricity through solar panels with experimental study methods in outdoor (sunlight) and indoor (lights) conditions. Experiments using two 500-watt (12000 Lux) incandescent lamps produced a maximum power of 5.25 watts at 35°C with an intensity of 94.8 W/m², while sunlight produced up to 13.93 watts of power at 55°C with an intensity of 206.6 W/m² using a 20 Wp polycrystalline panel. The power increases to the optimum temperature, then decreases due to thermal effects. Low temperature improves efficiency; high temperature lowers it. A 21.6 Ah (12 V) lithium-ion battery stores 259.2 Wh of energy, and with the slow charging method, it takes about 2 hours to reach the 20% discharge limit. Indoor testing with light lamps provides a more stable alternative. The increase in light intensity increases power to a certain point before decreasing due to temperature.